Surgical Management of Perianal Adenoma: A Case Report of Two Dogs - Sandeep Saharan; Anju Poonia; Sachin; Amit Kumar; Maneesh Sharma; Deepak Kumar Tiwari (Archives of Current Research International, 2024)
An eight and five years old intact male dogs presented with the history of straining, licking and scooting in the perianal region. This was noticed about five and two months respectively, prior presentation. Clinical examination revealed a circumscribed mass of 2 cm diameter in the Rottweiler dog and 7 cm in the non-descript dog in the perianal region. Haemato-biochemical parameters showed relative neutrophillia and anemia whereas survey radiography of lateral thorax revealed no metastasis. Surgical resection of the mass was done under general anesthesia. Histopathology revealed the growths as perianal adenoma. There was no reoccurrence, during the three months follow up of both dogs post surgery.